2024
DOI: 10.3390/ijgi13040112
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Spatial-Temporal Heterogeneity of Helplessness Sentiment and Its Built Environment Determinants during the COVID-19 Quarantines: A Case Study in Shanghai

Yuhao He,
Qianlong Zhao,
Shanqi Sun
et al.

Abstract: The COVID-19 outbreak followed by the strict citywide lockdown in Shanghai has sparked negative emotion surges on social media platforms in 2022. This research aims to investigate the spatial–temporal heterogeneity of a unique emotion (helplessness) and its built environment determinants. First, we scraped about twenty thousand Weibo posts and utilized their sentiments with natural language processing (NLP) to extract helplessness emotion and investigated its spatial–temporal variations. Second, we tested whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…Meanwhile, SVI data are publicly available and frequently updated to capture groundlevel panorama street scenes [114]. SVIs are an ideal dataset to comprehensively describe the urban environmental variability [115] and citizen behaviors, including building height [116], streetscape features [117], green and water systems [118], land-use classification [94,119,120], openness [121], road networks [122], mobile monitoring [98], mobility patterns [123,124], sun-glare-related traffic crashes [125], land use [79,[126][127][128], and residential behavior [129].…”
Section: Svis For Urban Form Modelingmentioning
confidence: 99%
“…Meanwhile, SVI data are publicly available and frequently updated to capture groundlevel panorama street scenes [114]. SVIs are an ideal dataset to comprehensively describe the urban environmental variability [115] and citizen behaviors, including building height [116], streetscape features [117], green and water systems [118], land-use classification [94,119,120], openness [121], road networks [122], mobile monitoring [98], mobility patterns [123,124], sun-glare-related traffic crashes [125], land use [79,[126][127][128], and residential behavior [129].…”
Section: Svis For Urban Form Modelingmentioning
confidence: 99%
“…Among them, a significant subset (280+ papers) has extensively utilized Street View Imagery (SVI) data [9] and artificial intelligence (AI) models, including machine learning (ML), deep learning (DL), and computer vision (CV) for urban-scale visual auditing [10][11][12]. Emerging studies [13][14][15][16] have indicated that street scene qualities significantly affect human behaviors, including running [17], walking [18], mental health [19][20][21], leisure activities [22], job and housing decisions [23,24], crime [25], and carbon emissions [26].…”
Section: Introduction 1public Space and Safety Perceptionmentioning
confidence: 99%